Dual-nozzle spray deposition process for improving the stability of proteins in polymer microneedles - Kim, Min Jung; Parka, Seok Chan; Choi, Seong-O (My University, 2017)
Polymer microneedles are an attractive way of transdermal delivery of various pharmaceutical compounds. Fabrication of drug-encapsulating polymer microneedles, however, often involves processing conditions unfavorable for maintaining the stability of drugs, including highly concentrated formulations, high temperature and long drying time. The stability of labile substances in biodegradable polymer matrices could also be significantly reduced by the use of organic solvents and emulsification. In this paper, we reported a new fabrication technique called the dual-nozzle spray deposition process, which utilizes a separate deposition of drug and polymer solutions, as a potential way to address the stability issue associated with current microneedle fabrication processes. A model protein, bovine serum albumin (BSA), was successfully incorporated into both water-soluble poly(vinyl alcohol) (PVA) and biodegradable poly(lactic-co-glycolic acid) (PLGA) microneedles by the dual-nozzle spray deposition process. The conformational change of BSA examined by circular dichroism and fluorescence spectroscopy suggests that the developed process helps maintain the structural stability of BSA during encapsulation in both PVA and PLGA matrices. We anticipate that the dual-nozzle spray deposition process would improve the stability of drugs by reducing adverse interaction with solvents and eliminating the emulsification process. Also, the developed process could be an attractive approach to fabricating polymer-based drug delivery devices.
Citation: Kim, M. J., Park, S. C., & Choi, S.-O. (2017). Dual-nozzle spray deposition process for improving the stability of proteins in polymer microneedles. RSC Advances, 7(87), 55350–55359. https://doi.org/10.1039/C7RA10928H